Recent Developments on Gas‐Phase Volatile Organic Compounds Abatement Based on Photocatalysis - Zhenmin Xu; Yuqing Ren; Xiaoming Deng; Mengli Xu; Wei Chai; Xufang Qian; Zhenfeng Bian (Advanced Energy & Sustainability Research, 2022)
The health and environmental problems caused by volatile organic compounds (VOCs) have attracted wide attention. Photocatalytic technology provides a green and sustainable way for VOCs removal. How to build a highly efficient and stable photocatalyst is of great significance to promote the practical application of photocatalysis technology. In this review, the literatures on photocatalytic oxidation in VOCs are surveyed and systematically categorized based on the types of photocatalytic materials. The methods of improving photocatalytic activity are studied, and the deactivation process of photocatalyst is discussed. Finally, the reaction mechanism is summarized according to the charge separation process and the classification of reactive oxygen species.